The Role of Digital Marketing in SMEs : A Literature Review - Supriadi, Yudi Nur (Garuda Prestasi Nusantara Consulting, 2024)
Digital marketing has become one of the factors that drives the improvement of company performance. This study aims to determine the role of digital marketing in SMEs. SMEs are currently experiencing very rapid growth and have become the mainstay of the Indonesian economy. The method used in this study is literature review. The results of the study indicate that digital marketing can improve the performance of SMEs. Digital marketing makes it easier for SMEs to market products and reach consumers more widely.